Major aspects of STEM education based on U.S. government initiatives - Batyuk, Liliya (Educational Challenges, 2025)
Purpose. The article is devoted to the study and historical and pedagogical analysis of the development and current state of STEM education in the United States of America, and with the identification of features, and significant changes in the regulatory framework, content, forms and methods of implementing STEM education in the USA. Studying the experience of the United States in the development of the STEM education sector, based on Federal Government initiatives, and studying the experience of training STEM specialists, can contribute to bringing the quality of Ukrainian education closer to international standards. Methodology. The methodology includes specific-search and logical-synthetic analysis (for collecting, analyzing, systematizing and generalizing the provisions of historical, scientific-pedagogical, periodical, methodological, reference literature, and regulatory documentation); and system-structural analysis (for systematizing scientific facts about education and STEM education in the USA). In addition, we carried out chronological analysis (for describing the stages of development and highlighting the periods of reform of STEM education in the USA); statistical analysis (collection, processing, analysis of US educational statistics data); and comparative analysis of individual aspects of the development of STEM education in the USA. Theoretical-generalizing method and interpretation method (for formulating and substantiating conclusions based on the results of the study) were also used. Results. It is proven that during the second half of the 20th and early 21st centuries STEM education as a separate field has not only received Federal support and funding from the US government, but has also become a national priority of US public education policy, at each stage of development presented in the study. Conclusions. Recognizing the decline in the literacy rate of the United States population in the second half of the 20th century and the increase in the gaps in the knowledge, skills, and professional competences of specialists in various fields, the US Government has made every effort to correct the situation. It adopted step by step a number of Laws that have become the basis and building blocks in building a STEM educational environment. There was the large-scale implementation of educational reforms in the US, innovations, and investments in those areas that worked to improve STEM teaching and learning, resulting in the coverage of STEM education by a larger part of society and the implementation of the «Education for All» strategy. It led to the wide access of the US population to high-quality continuing STEM education, and the country’s achievement of leading positions in the field of STEM literacy, STEM innovations, and STEM professions.